Coupling of muscarinic receptors to protein kinase C underlies a feedback regulation of cell responsiveness to acetylcholine - Dymova, Ekaterina A.; Rogachevskaja, Olga A.; Sokolov, Vladislav V.; Kopylova, Elizaveta Е.; Kabanova, Natalia V.; Kolesnikov, Stanislav S. (Biochimica et biophysica acta. General subjects, 2025)
Acetylcholine (ACh)-induced Ca2+ signaling was analyzed in HEK-293 (WT-HEK) cells and their derivatives, IP3R1-HEK, IP3R2-HEK, and IP3R3-HEK with a single functional IP3 receptor isoform, IP3R1, IP3R2, or IP3R3, respectively. The initial stimulation of WT-HEK cells triggered a prolonged feedback process that diminished their responsiveness to ACh. Inhibition of protein kinase C (PKC) with Gö 6983 or calphostin C prevented the decline of ACh responsivity, indicating that PKC was involved. Using IP3R1-HEK, IP3R2-HEK, and IP3R3-HEK cells, it was shown that PKC was capable of regulating Ca2+ release through each IP3R isoform. While in control, IP3 uncaging triggered Ca2+ transients in ∼15 % of cells loaded with caged-Ins(145)P3/PM, PKC inhibition enlarged this fraction nearly twofold. These observations suggested that in ACh transduction machinery, PKC targeted primarily IP3-driven Ca2+ release. ADP and 5-HT triggered Ca2+ transients in WT-HEK cells and CHO cells expressing endogenous P2Y and recombinant 5HT2C receptors, respectively. The responsiveness of WT-HEK cells to ADP and CHO cells to 5-HT applied serially declined after the initial cell stimulation but PKC inhibition precluded this phenomenon almost completely. The coupling of GPCRs to PKC in living cells, muscarinic and P2Y receptors in WT-HEK cells and 5HT2C receptors in CHO cells, was demonstrated for the first time using real-time fluorescence imaging and sapphireCKAR, a genetically encoded sensor of PKC activity. Altogether, our findings suggest that a PKC-based feedback regulation of agonist-induced Ca2+ release might be a common attribute of transduction of various agonists involving GPCRs coupled to the phosphoinositide cascade. •ACh mobilized Ca2+ in HEK-293 cells in an “all-or-nothing” manner.•The inhibition of PKC with Gö 6983 or calphostin C prevented the decline of cell responsivity to ACh.•The coupling of muscarinic receptors to PKC was demonstrated using the genetically encoded sensor of PKC sapphireCKAR.•IP3R mediated Ca2+ release was the most likely target of PKC in ACh transduction machinery.